A service-oriented framework for controlling invasive species in agriculture. (2nd June 2009) - Medjahed, Brahim; Hadi, Shamil; Grosky, William I.
The Emerald Ash Borer (EAB) has killed or infested millions of ash trees in the USA. It has the potential to decimate ash trees as a component of North American forests, which will have dramatic ecological and economic effects. Government agencies have joined forces to implement a long-term programme to contain and eventually eradicate the borer. One key requirement for the success of this programme is the underlying information-sharing infrastructure. In this paper, we propose an ontology-based service-oriented framework, called Sentinel, to automate the dissemination of EAB-related information. We also present experiment results to assess the performance of our framework.